2012
DOI: 10.1111/j.2042-3306.2012.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a constant‐rate infusion of dexmedetomidine on the minimal alveolar concentration of sevoflurane in ponies

Abstract: A dexmedetomidine CRI at the reported dose significantly reduces the MAC of sevoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
(69 reference statements)
2
30
2
1
Order By: Relevance
“…Dexmedetomidine induces antinociception in conscious dogs, cats, rats and human beings (Sabbe et al, 1994;Slingsby et al, 2009;Aydogan et al, 2013;Kosharskyy et al, 2013) and reduces the requirements for inspired anaesthetic gas in dogs (Pascoe et al, 2006;Uilenreef et al, 2008), cats (de Souza et al, 2010 and horses (Gozalo-Marcilla et al, 2013a, 2013b, 2013c. In the present study, we determined the antinociceptive effects of dexmedetomidine infusions in conscious horses.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Dexmedetomidine induces antinociception in conscious dogs, cats, rats and human beings (Sabbe et al, 1994;Slingsby et al, 2009;Aydogan et al, 2013;Kosharskyy et al, 2013) and reduces the requirements for inspired anaesthetic gas in dogs (Pascoe et al, 2006;Uilenreef et al, 2008), cats (de Souza et al, 2010 and horses (Gozalo-Marcilla et al, 2013a, 2013b, 2013c. In the present study, we determined the antinociceptive effects of dexmedetomidine infusions in conscious horses.…”
Section: Discussionmentioning
confidence: 89%
“…α-2 Agonists are used as constant rate infusions (CRI) during anaesthesia to provide antinociception and to reduce the requirement for inhaled anaesthetic agents in horses (Bettschart-Wolfensberger et al, 2001Gozalo-Marcilla et al, 2013a, 2013b, 2013c. Antinociception with dexmedetomidine is mediated primarily through α-2a receptors in the spinal cord (Yaksh, 1985;Takano and Yaksh, 1991;Guo et al, 1996;Zhao et al, 2013), but an effect within the locus coeruleus also produces antinociception (Guo et al, 1996;Funai et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, others reported that medetomidine CRI reduced the MAC of desflurane by 28% [16] and that dexmedetomidine CRI reduced the MAC of sevoflurane by 53% [22] in experimental ponies. These results indicate that experimental MAC reduction study is desirable to detect correct anesthetic-sparing effects.…”
Section: Discussionmentioning
confidence: 92%
“…It is often administered as a continuous rate infusion (CRI), either to treat painful conditions or to decrease the amount of inhalation anaesthetics during general anaesthesia (Gozalo-Marcilla et al 2013, Gozalo-Marcilla et al 2015. Three escalating CRI doses (2, 4, and 6 µg/kg/h) were investigated to determine which CRI is the minimal necessary to provide consistent antinociception in conscious horses (Risberg et al 2014).…”
Section: Alpha-2 Agonistsmentioning
confidence: 99%